In vitro Effect of Withania somnifera, Mucuna pruriens and Pausinystalia johimbe on Hepatic Cytochrome P450 in Rat - Sultana, Rajia; Sultan, Md Zakir (Bangladesh Pharmaceutical Journal, 2018)
The effect of Withania somnifera, Mucuna pruriens and Pausinystalia johimbe extracts on hepatic cytochrome P450 enzyme CYP3A4 activities was studied using rat liver microsomes. CYP3A4- dependent testosterone 6β-hydroxylation activities were determined by ELISA. In the study, rats were treated with W. somnifera (0.5 g/kg/day), M. pruriens (0.5 g/kg/day) and P. johimbe (0.25 g/kg/day) extracts for 20 days. It was found that W. somnifera, M. pruriens and P. johimbe extracts showed potent to moderate inhibitory effect on CYP3A4 activities in rat liver microsomes, with IC50 values of 18.01 ng/mL, 14.93 ng/mL and 21.03 ng/mL, respectively. Bangladesh Pharmaceutical Journal 21(2): 118-122, 2018